Financial Market Integration within the European Union (Economic and Political Thought, 2010)
The aim of the article is to present the process of financial market integrationwithin the European Union and its assessment.The article explains the concept of financial integration and presents stepstaken by the European Union in order to integrate the financial market andthe level of that integration, and also indicates challenges that the EuropeanUnion must meet to further integrate its financial market.The analysis that was carried out lets the author state that the attemptsto create a uniform financial market within the European Union have beenunsuccessful so far. Nevertheless, the steps taken by the European Union, i.e.the implementation of FSAP, the introduction of the euro, common financialpolicy, TARGET or SEPA, greatly contributed to the increase of the level ofthe EU financial market integration. The development of the integration canbe especially seen on the wholesale financial services market. Retail marketkeeps being poorly integrated. The 21st century financial crisis clearly showedthat the process of integration requires an introduction of some changeswhich mainly regard the issues of financial market supervision.